PENGARUH PROFITABILITAS, FLEKSIBILITAS KEUANGAN, UKURAN PERUSAHAAN, TANGIBILITAS, DAN LIKUIDITAS TERHADAP STRUKTUR MODAL - AFRIZAL ARI JOTIVIAN; BENY BENY (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2025)
This study aims to analyse the factors that influence capital structure. The factors analysed include profitability, financial flexibility, company size, tangibility, and liquidity. The object of this research is energy companies listed on the Indonesia Stock Exchange (IDX) during the period 2013-2023. This study uses a quantitative approach with a causal method, where the sample consists of seven companies selected through Purposive Sampling technique, resulting in a total of 77 observation data. The data used was obtained from the company's financial statements and analysed using EViews12 to test and evaluate the relationship between variables. The results reveal that financial flexibility, firm size, and liquidity have a significant influence on capital structure, while profitability and tangibility show no influence on capital structure.